Geophysical reconnaissance of the western basin of the Plaine du Nord aquifer, Haiti - Miner, Wm. Javan; Adamson, James K.; Hasbrouck, James C.; Monforte, Sergio Perez; Vera, María Rodriguez (Hydrogeology journal, 2022)
A geophysical reconnaissance was conducted to support aquifer characterization and evaluate groundwater potential in the western portion of the Plaine du Nord aquifer to provision the growing water demands of the city of Cap-Haitien in the Republic of Haiti. Hybrid-source audio-magnetotelluric (HSAMT) soundings and gravity measurements were collected to support the Government of Haiti in sourcing additional water supplies for the city. The Plaine du Nord aquifer is poorly characterized considering it is one of Haiti’s largest aquifers, few drilling logs are available, and only one borehole has investigated the deeper extents of the aquifer. HSAMT supports depth profiling of subsurface resistivity, which supports interpretations of geological strata and groundwater conditions. Gravity measurements allow for complementary mapping of Earth density anomalies and contrasts, which assist in interpreting aquifer thicknesses or depth to bedrock. Pairing HSAMT and gravity methods permitted both an estimation of aquifer thickness and relative changes in sediment characteristics. Gravity results allowed for the mapping of aquifer thickness across the study area, with interpreted thickness greater than 300 m in the coastal zone. HSAMT results cross correlated with available well records and enabled the delineation of zones with increased groundwater potential. The results of the combined methods indicate groundwater storage potential of freshwater in deeper alluvium and emphasize the importance of strengthening resource characterization, modelling and monitoring to guide sustainable resource development and management.